2023
DOI: 10.3390/biomedicines11051447
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Attenuate Liver Injury by Modulating Antioxidant Activity and Inflammatory Cytokines in Thioacetamide-Induced Liver Cirrhosis in Rats

Ahmed A. J. Jabbar,
Zaenah Zuhair Alamri,
Mahmood Ameen Abdulla
et al.

Abstract: Sinapic acid (SA) is a natural pharmacological active compound found in berries, nuts, and cereals. The current study aimed to investigate the protective effects of SA against thioacetamide (TAA) fibrosis in rats by histopathological and immunohistochemical assays. The albino rats (30) were randomly divided into five groups (G). G1 was injected with distilled water 3 times/week and fed orally daily with 10% Tween 20 for two months. G2–5 were injected with 200 mg/kg TAA three times weekly for two months and fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Our finding showed that the AFM 1 group noticed widespread localization of caspase-3 protein throughout the hepatorenal tissues. AFM 1 -induced ROS generation, as previously discussed, increases the permeability of the mitochondrial membrane and opens the transition pores, resulting in cytochrome c release to the cytosol, which initiates activation of caspase cascade ends with caspase-3 activation (Mariod et al 2023 ; Jabbar et al 2023b ). The caspase-3 is a protein member of the cysteine-aspartic acid protease family and is the end product of caspase activation (Hassanen et al 2023a ).…”
Section: Discussionmentioning
confidence: 97%
“…Our finding showed that the AFM 1 group noticed widespread localization of caspase-3 protein throughout the hepatorenal tissues. AFM 1 -induced ROS generation, as previously discussed, increases the permeability of the mitochondrial membrane and opens the transition pores, resulting in cytochrome c release to the cytosol, which initiates activation of caspase cascade ends with caspase-3 activation (Mariod et al 2023 ; Jabbar et al 2023b ). The caspase-3 is a protein member of the cysteine-aspartic acid protease family and is the end product of caspase activation (Hassanen et al 2023a ).…”
Section: Discussionmentioning
confidence: 97%
“…Pinostrobin was mixed with 10% Tween 20 and delivered to rats in an amount of 5 mL/kg in two different doses, 30 and 60 mg/kg. 37 …”
Section: Methodsmentioning
confidence: 99%
“…37 Sinapic acid also showed anti-fibrotic properties of the liver against thioacetamide-induced liver fibrosis. 38 Gallic acid, which was identified in the n-butanol fraction and residual aqueous fraction by HPLC-DAD, is known for its antioxidant power and effective antiinflammatory properties. 39 Studies have shown that gallic acid significantly lowers the level of hepatic parameters ALT, AST, PAL, GGT, total and conjugated bilirubin, and the level of MDA and allows restoration of the endogenous antioxidant system in rats/mice poisoned with diethylnitrosamine, 40 and paracetamol.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%